Simultaneous optical recording of action potentials and calcium transients in cardiac single cells differentiated from type 1 CPVT-iPS cells - Takaki, Tadashi; Tamura, Norihisa; Imahashi, Kenichi; Nishimoto, Tomoyuki; Yoshida, Yoshinori (Frontiers in Physiology, 2025)
Numerous reports investigating channelopathies, including Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT), have successfully reproduced using cardiomyocytes (CMs) differentiated from human induced pluripotent stem cells (hiPSCs). However, the relationship between action potentials (AP) and calcium transient waveforms—especially after drug treatment—remains unclear. In this study, we simultaneously loaded a membrane potential dye FluoVolt and the new calcium indicator CalbryteTM 590 AM and optimized stimulation and detection of both dyes to successfully obtain a higher signal-to-noise (S/N) ratio than the conventional membrane potential dye-red fluorescence Ca2+ dye combination, thus enabling the simultaneous recording of both AP and calcium transient waveforms in single hiPSC-CMs, which continued even after gradual increases in drug concentration. In drug-loading experiments on CPVT1 (RyR2-I4587V) hiPSC-derived ventricular-like CMs, carvedilol and flecainide demonstrated some effectiveness, while JTV519 at 3 µM exhibited both efficacy and alterations in AP waveforms. The Ca2+/calmodulin-dependent serine-threonine protein kinase II (CaMKII) inhibitor KN-93 at 1 µM was highly effective (93%) at reducing Ca2+ transient abnormalities without altering AP waveforms.